Proposed Marketing Strategy to Increase Sales By Increasing Brand Wareness Of Water & Wastewater Treatment Company (PT Dwikarya Mitra Sejati) - Irfan Yusuf Saputro; Mustika Sufiati Purwanegara (Journal of Economics and Business UBS, 2023)
PT Dwikarya Mitra Sejati is a company in the form of a Limited Liability Company and is engaged in trading chemicals and services. Where its existence is needed as a company engaged in the distribution and trading of chemicals. It has a chemical storage warehouse in Tangerang. PT Dwikarya Mitra Sejati, the company has a problem with declining sales in every year. PT Dwikarya Mitra Sejati offers a wide range of chemicals to meet industrial needs. However, PT Dwikarya Mitra Sejati has not been optimal in terms of product marketing. So, it can be assumed that the cause of the decline in the company's sales is the absence of a clear and optimal marketing strategy plan. The purpose of this research is to analyze the external and internal business conditions at PT Dwikarya Mitra Sejati so that they can find out the root problems experienced and can implement marketing programs that can increase the company's income. The qualitative method that will be applied in this research is collecting primary and secondary data through internal and customer interviews from PT Dwikarya Mitra Sejati. The main reason for the decline in the percentage of company sales is the absence of a marketing strategy implemented by PT Dwikarya Mitra Sejati. In this research; PETEL analysis, Porter’s 5 Forces, and Customer analysis is used for external analysis. Meanwhile, for internal analysis, Marketing Mix 4p was used, VRIO analysis, purchase analysis. From the results of this study it is suggested that companies make brands easier to recognize and remember as well as build customer trust in these brands and increase sales with STP Strategy, POS Marketing Strategy, and Conventional Marketing Strategy.